Occult Pneumothorax Identification on Extended Focused Assessment with Sonography for Trauma Examination in Children. Issue 10 (October 2021) - Malek, Daniel; Santillanes, Genevieve; Hsiao, Victor; Mailhot, Thomas; Claudius, Ilene
Abstract : Objective: Occult pneumothoraces (OPTXs) are defined by air within the pleural space that is not visible on conventional chest radiographs (CXR). The aim of this study was to understand how frequently the Extended Focused Assessment with Sonography for Trauma (eFAST) examination identifies occult PTX in a pediatric blunt trauma population as compared with a criterion standard of chest computed tomography (CCT). Methods: This study is a secondary analysis of blunt trauma patients younger than 18 years who underwent CCT at Los Angeles County +USC Medical Center Emergency Department from October 2015 to April 2017. The eFAST examination was performed and documented by an emergency medicine resident with attending oversight or by an emergency medicine attending for each trauma. The eFAST results were reviewed for patients diagnosed with small or trace pneumothoraces identified on CCT. Results: Of 168 pediatric trauma patients undergoing CCT, 16 had OPTXs not seen on CXR and 4 patients had a small/trace PTX without a corresponding CXR performed. None were identified on eFAST. Conclusions: Although the sample size in this data set was small, our eFAST examinations identified none of 16 proven and 4 presumed OPTXs. The standard eFAST examination performed poorly in the detection of OPTXs in this single-center study of pediatric blunt trauma victims.